Influence of sales promotions on online purchase decisions and post-purchase evaluations of young adults in NCR - Licerio, Julia Andrea P. (College of Home Economics, University of the Philippines Diliman, 2023)
The widespread use of online sales promotion, as a result of the rapid growth of ecommerce in the Philippines, has been attracting consumers to purchase products regularly and abundantly. However, it is still unclear which specific benefits of sales promotions have the strongest influence on consumers’ purchase decisions. Therefore, this study aimed to examine the influence of sales promotions on the online purchase decision and post-purchase evaluations of young adults in NCR. A mixed qualitative and quantitative approach was used. The study utilized an online survey questionnaire to collect data from 160 young adults, along with in-depth interviews with 20 respondents. The data gathered were analyzed through descriptive and inferential statistics, and thematic analysis. The results showed that sales promotion benefits influenced online purchase decisions to varying degrees. Monetary savings had a strong influence on purchase decisions, while improved shopping convenience had almost no influence. Higher product quality and developed value expression moderately influenced purchase decisions. Moreover, no significant differences were observed in the influence of sales promotions across demographic variables including age, sex, and income. Additionally, sales promotions were found to have an effect on consumers' spending practices and budgets, leading them to impulse buy and overbudget, respectively. However, sales promotions also helped consumers to stay within their budgets and maximize their savings. Consumers expressed high satisfaction with purchases using online sales promotions. The perceived advantages of sales promotions include budgetary benefits, more quantity, more options, and convenience. The perceived disadvantages include overspending, functional risks, overbudgeting, and time constraints. Based on these results, future research could explore other benefits of sales promotions, examine other demographic factors, and identify measures to mitigate the risks of the use of online sales promotions.